Effect of passive ultrasonic agitation during final irrigation on cleaning capacity of hybrid instrumentation - Marcilene Coelho Vinhorte; Eduardo Hideki Suzuki; Maíra Sousa de Carvalho; André Augusto Franco Marques; Emílio Carlos Sponchiado Júnior; Lucas da Fonseca Roberti Garcia (Korean Academy of Conservative Dentistry, 2014)
Objectives To evaluate the effect of passive ultrasonic agitation on the cleaning capacity of a hybrid instrumentation technique. Materials and Methods Twenty mandibular incisors with mesiodistal-flattened root shape had their crowns sectioned at 1 mm from the cementoenamel junction. Instrumentation was initiated by catheterization with K-type files (Denstply Maillefer) #10, #15, and #20 at 3 mm from the working length. Cervical preparation was performed with Largo bur #1 (Dentsply Maillefer) followed by apical instrumentation with K-type files #15, #20 and #25, and finishing with ProTaper F2 file (Denstply Maillefer). All files were used up to the working length under irrigation with 1 mL of 2.5% sodium hypochlorite (Biodynâmica) at each instrument change. At the end of instrumentation, the roots were randomly separated into 2 groups (n = 10). All specimens received final irrigation with 1 mL of 2.5% sodium hypochlorite. The solution remained in the root canals in Group 1 for one minute; and ultrasonic agitation was performed in Group 2 for one minute using a straight tip inserted at 1 mm from working length. The specimens were processed histologically and the sections were analyzed under optic microscope (×64) to quantify debris present in the root canal. Results The samples submitted to ultrasonic agitation (Group 2) presented significant decrease in the amount of debris in comparison with those of Group 1 (p < 0.05). Conclusions The hybrid instrumentation technique associated with passive ultrasonic agitation promoted greater debris removal in the apical third of the root canals.